Visceral variations in adult intestinal malrotation: A case-series study - Şahin, Şükrü; Gedik, Mehmet (Journal of Surgery and Medicine, 2020)
Aim: Intestinal malrotation (IM) is a very rare rotational anomaly of midgut. Although uncommon, failure to diagnose IM may lead to devastating consequences. It is important that radiologists and surgeons are made aware of the diagnosis of adult IM and accompanying variations. Since IM is usually reported as a case report, it is important to note the frequency of the accompanying variations. It is aimed to present radiological findings of intestinal malrotation, increase awareness of abdominal variations and pathologies accompanying adult IM and reduce diagnostic failure. Methods: Thirty-two patients aged over 18 years, who underwent computed tomography (CT) and received a diagnosis of IM, were retrospectively evaluated in terms of CT findings. Aplasia or hypoplasia of the uncinate process of the pancreas, focal thickening areas that may cause suspicion of a pseudomass, location of the superior mesenteric vein relative to the superior mesenteric artery, localization of the cecum, and the frequency of a redundant sigmoid colon were determined. Results: The frequency of IM in adults undergoing CT was 1/5,375. In two of 32 cases, the cause of acute abdomen was identified while the other cases were detected incidentally. Aplasia or hypoplasia of the uncinate process of the pancreas and a redundant sigmoid colon were detected in 21 (65.6%) and 23 (71.9%) cases, respectively. The cecum was in the normal location in eight patients (25%), and there was a normal superior mesenteric artery-vein relationship in six (18.8%). Conclusion: Intestinal malrotation is rarely encountered in adults and most cases are incidentally detected. IM is often accompanied by aplasia or hypoplasia of the uncinate process of the pancreas. A normal superior mesenteric artery-vein relationship and the cecum in the normal position are seen in one out of every four to five cases.